2013
DOI: 10.1016/j.clim.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis patients exhibit impairment of the high potency CCR5+ T regulatory cell subset

Abstract: CCR5 expression on CD4+CD25highFoxp3+ regulatory T cells (Tregs) has been reported to be crucial for limiting Th1 inflammation associated with autoimmunity and bacterial infections. We inquired whether abnormalities in chemokine receptors expressed on Tregs might be involved in the psoriatic pathogenesis. Indeed, the proportion of CCR5+Treg was 58.8% in healthy individuals (n=9), whereas only half as many CCR5+Treg cells were found in psoriatic individuals (29.1%, n=8, p<0.01). The flow-enriched control CCR5+T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 34 publications
3
32
0
2
Order By: Relevance
“…Recently, we have reported positive correlations between circulating Treg cell counts in patients with AD and T-cell activation. 33 Moreover, although it is known that Treg cells in patients with psoriasis are dysfunctional, 73,74 Ou et al 75 have shown that circulating Treg cells are functional in patients with AD. Thus in addition to possibly indicating higher systemic inflammation in patients with AD, 33 increased transitional B-cell counts might participate in converting CD4 1 T cells into functional Treg cells, whereas their significantly low counts in patients with psoriasis and lack of IFN-g suppression might indicate reduced suppressive capacity and contribute to the dysfunctional state of Treg cells in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we have reported positive correlations between circulating Treg cell counts in patients with AD and T-cell activation. 33 Moreover, although it is known that Treg cells in patients with psoriasis are dysfunctional, 73,74 Ou et al 75 have shown that circulating Treg cells are functional in patients with AD. Thus in addition to possibly indicating higher systemic inflammation in patients with AD, 33 increased transitional B-cell counts might participate in converting CD4 1 T cells into functional Treg cells, whereas their significantly low counts in patients with psoriasis and lack of IFN-g suppression might indicate reduced suppressive capacity and contribute to the dysfunctional state of Treg cells in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Unrestrained function of T cells in psoriasis may also be due to the dysfunction of T reg cells. In fact, some studies have shown that T reg cells isolated from psoriatic patients have a decreased suppressive function [56,57], others demonstrated that they produce IFN-γ, TNF-α, and IL-17, suggesting a switch of their function from suppressive to proliferative [58]. …”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Soler and colleagues (2013) also pointed the connection between IL17 and FOXP3. They defended that Treg cells in psoriasis readily turn into IL-17-expressing cells [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Several researchers found decreased CD4 + CD25 + FOXP3 + T circulating cells both numerically and functionally in psoriasis patients [14, 15]. In order to balance the deficient anti-inflammatory response, clinical trials have been done using IL-10 recombinant human (rh) therapy protocols [16].…”
Section: Introductionmentioning
confidence: 99%